2019
DOI: 10.1002/glia.23678
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of homeostatic and disease‐associated‐microglial genes by IRF1, LXRβ, and CEBPα

Abstract: Microglia transform from homeostatic to disease‐associated‐microglia (DAM) profiles in neurodegeneration. Within DAM, we recently identified distinct pro‐inflammatory and anti‐inflammatory sub‐profiles although transcriptional regulators of homeostatic and distinct DAM profiles remain unclear. Informed by these studies, we nominated CEBPα, IRF1, and LXRβ as likely regulators of homeostatic, pro‐inflammatory and anti‐inflammatory DAM states and performed in‐vitro siRNA studies in primary microglia to identify r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 63 publications
(124 reference statements)
5
52
0
Order By: Relevance
“…Intriguingly, ERK1/2 was recently shown to mediate microglial phenotype that increases pro‐inflammatory while suppressing anti‐inflammatory and homeostatic genes in disease associated‐microglia (DAM; Gao et al, ), supporting our notion of microglial polarization to extended pro‐inflammatory phenotype. Our cytokine data demonstrates that activation of PARP‐1/TRPM2 axis promotes pro‐inflammatory cytokines (ICAM1, IL‐1α, IL‐7, GM‐CSF, M‐CSF, MIG), without promoting anti‐inflammatory cytokines (IL‐10, IL‐13, MIP1α, MIP1γ, PF‐4) in order to retain homeostasis.…”
Section: Discussionsupporting
confidence: 76%
“…Intriguingly, ERK1/2 was recently shown to mediate microglial phenotype that increases pro‐inflammatory while suppressing anti‐inflammatory and homeostatic genes in disease associated‐microglia (DAM; Gao et al, ), supporting our notion of microglial polarization to extended pro‐inflammatory phenotype. Our cytokine data demonstrates that activation of PARP‐1/TRPM2 axis promotes pro‐inflammatory cytokines (ICAM1, IL‐1α, IL‐7, GM‐CSF, M‐CSF, MIG), without promoting anti‐inflammatory cytokines (IL‐10, IL‐13, MIP1α, MIP1γ, PF‐4) in order to retain homeostasis.…”
Section: Discussionsupporting
confidence: 76%
“…In particular, ERK was found to positively regulate several canonical DAM genes, including Ccl3, Ch25h, Spp1, Igf1, and Itgax (Supplemental Figure S2) and pro-inflammatory DAM genes, including Ccl2, Irf1, Tnf, Slamf9, and Cd69 (Supplemental Figure S3). We also calculated a synthetic eigenvalue to represent overall expression of homeostatic, anti-inflammatory DAM and pro-inflammatory DAM profiles across each experimental condition using previously identified hub genes (Kme>0.75) of each microglial profile that were present in our Nanostring dataset (Dai et al, 2018; Gao et al, 2019). We confirmed that inhibition of ERK activity suppresses homeostatic, anti-inflammatory as well as pro-inflammatory DAM gene expression while IFNγ increases pro-inflammatory DAM and suppresses anti-inflammatory DAM gene expression (Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
“…Primary microglia cultures were prepared from P0-3 post-natal mouse brains as previously described (Gao et al, 2019). Briefly, brain tissue was harvested from C57BL/6J mice (P0 to P3) and digested with Trypsin for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations